PROBLEMATIKA MEWUJUDKAN KEADILAN SUBSTANTIF DALAM PENEGAKKAN HUKUM DI INDONESIA - Anwar, Anwar (Jurnal Konstitusi, 2010)
Theoretically, the problems deal with the attitude of the law enforcers, especially the judges, to take sides in considering the procedural or substantive justices. The 1945 Constitution or the legislation on the justice power and on Constitutional Court of Law actually oblige the judges to realize the substantial justice in law enforcement. The judges are not the sounders of the laws, since human beings are never able to make perfect legislation. It is the judges who should interpret the legislations in order to realize the substantial justice.